Studi Kasus Analisis Kerusakan Abutmen Jembatan Sungai Bahalang Kalimantan Tengah - Gawit Hidayat (Jurnal Teknologi Berkelanjutan, 2012)
Bahalang Bridge is a Class B truss bridge crossing the Bahalang River in Ampah (Central Kalimantan). Itwas built to connect roads for coal transportation. The bridge structure has a problem, namely an abutment failure in itseast-side abutment. There has been a 30-degree rotation that the back side of abutment has moved about 2 metersdownward and slipped from its place about 1 meter to the river. The purpose of this study is to study the behavior of thesoil layers around the abutment and to find out the main cause of failure. The analysis is based on approximatecalculation using Plaxis and Xstabl computer packages. Two options of calculation are considered. In the first option awater level of29.5 m is used. Xstabl shows an SFmin of 0.764 and Plaxis shows a total displacement of 64.5 m. In thesecond one the water level of the river is assummed to be 27.4 m. Xstabl shows an SFmin of 0.807 and Plaxis shows atotal displacement of 4.15 m. The results suggest that the collapse already took place during the backfill activity on theeast-side approach road. During that process the backfill material consisting of sand was laid too rapidly by directdumping from truck and spreading by excavator.s. The total displacement is 6.45 m. The pile bending moments aerfound to be above the allowable value, that is 57.81 kNm in front of the piles, and 63.90 kNm on the back. It can beconcluded that the failure is due to excessive displacement that has. the potential to damage the piles.